Investigação do papel de compostos de telúrio (iv) e nitroalcenos na epilepsia induzida por lítio-pilocarpina - Predebon, Gabriela de Melo [UNIFESP] (2016)
Introduction: Epilepsy is a disorder characterized by the propensity of the brain to generate seizures and the temporal lobe epilepsy (TLE) is the most common type. The hippocampal sclerosis (HS) is the main pathophysiological feature of TLE. The experimental model of epilepsy induced by lithium pilocarpine (LiPilo) reproduces the main pathophysiolocal characteristics of human TLE. It is increasing the number of researchers interested in identifyng new therapeutic targets for treat drug-resistent seizures. In this study, the effect of compounds of Tellurium (Te) and Nitroalkenes (Nitro) were tested for neuroprotective and anticonvulsant effects in the LiPilo model of epilepsy. These compounds had beneficial effects in models of inflammatory, cardiovascular and neurodegenerative diseases being promising molecules for the treatment of TLE.Aims:Evaluate the effects of the TeCG (Dichloro(E)-1-(1-chloro-2-(4-methoxyphenyltellanyl)vinyl)cyclohexanol), Nitro-1 ((E)-1-nitro-4-(2-nitrovinyl)benzene) and Nitro-13 ((E)-1nitro-4-(2nitroprop-1-en-1-yl)benzeno) after SE induced by LiPiloon their ability to modify the epileptogenesis.Methods: The cytotoxicity of TeCG, TeC, Nitro-1 and Nitro-13 was evaluated in C-12 cells by concentration-response curves (0.1?M to 50?M). The cell protection property of the compounds was analyzed by means of flow cytometry with labeling of propidium iodide, after incubation of the cells with the aggressive agent hydrogen peroxide (H2O2, 30?M).Permeability of TeCwere analyzed in vitro(0.1?M)at different times 2, 5, 24 and 48 hours, and in vivo (0.04mg/ kg, i.p.) was applied 30 minutes after beginning of SE. Electroencephalographic (EEG) was used to evaluate the ability of TeCG (0,04mg/kg, i.p), Nitro-1 and Nitro-13 (2mg/kg, i.p) to block behavioral seizures. Neuronal cell death in hippocampal sub-regions (CA1, CA3 and Hilo) was analyzed by Fluoro-JadeB (FJ-B) in the following groups: Control, Pilo+Vehicle, Saline+TeCG, Saline+Nitro-1, Saline+Nitro-13, Pilo+TeCG, Pilo+Nitro-1 and Pilo+Nitro-13. Results:Our results showed that TeCG and TeC at doses below 10?M and 50?M, respectively, had no toxic effects. TeCG had cytoprotective effect against H2O2 at concentrations of 0.1?M and 1?M. TeC crossed the plasmatic membrane of PC-12 cells after 2 hours of incubationand the blood brain barrier of Wistar rats after 24 hours from the beginning of SE. Nitro-1 and Nitro-13 had non-toxic effect below at 40?M and both compounds had cytoprotective effect against H2O2in concentration of 0.1?M. TeCG treatment did not change the electroencephalographic seizures, but had neuroprotective effect in the hippocampal subfields CA1, CA3 and Hilo. Nitro-1 had neuroprotective effect in CA3 and Hilo, and Nitro-13 caused neuroprotection in CA1, CA3 and Hilo. Conclusion:The compounds TeCG, Nitro-1 andNitro-13 presented cytoprotective effects of PC-12 cells incubated with the deleterious agent H2O2.They also presented neuroprotective effect in hippocampal brain areas of rats subjected to LiPilo model. These compounds should be better evaluated for the potential seizure-modifying effects.